“valoración económica con fines turísticos de la naciente del rio tioyacu, provincia de rioja-región San Martín” - Reátegui Alegría, Gina Isabel (2014)
The objective of the present work was to value economically with tourist ends the Source of the Tioyacu river to the development of the tourist activity through the Contigent Valuation Method because it is the appropriate one to value the services of recreation and its application allowed to obtain the economic value of the Source of Tioyacu associated to the landscape benefit in front of a quality, being the disposition to pay SI. 38.72 by each visitor tourist per year, in the model 1 estimated by LOGIT, it corroborated so the utility of such method in the value of the environmental services given by this Source. This value is important enough as to justify not only the existence and the conservation of this natural area, but of the fluency of public that nowadays visits this important tourist site. lt is necessary to extend the services that at the present time are given. This recommendation will allow to give a better service to the tourist that arrive to this part of the region, at the same time the services that are given do not cover the demand of this natural attraction in general. lt is necessary to have into account that to value this environmental service, associating a monetary number does not pretend to give a price but is the reflection of the value that represents to the users this attraction.